PRINCIPLES OF RESTORATION OF CULTURAL HERITAGE IN THE CONDITIONS OF POST-WAR RECONSTRUCTION OF UKRAINE - Oliinyk, Olena; Chyzhevskyi, Oleksandr (Theory and practice of design, 2024)
Goal. This article examines the principles of preserving and restoring the cultural heritage of Ukraine in the conditions of post-war reconstruction. Methodology. The following methods are used in the article: analysis of the international experience of post-war restoration and collection of data that will make it possible to understand modern trends in heritage restoration and ensuring its sustainable preservation; a review of available research on the restoration of destroyed heritage. The research is based on published information on the history of design, restoration and exploitation of restored cultural heritage, analysis of international and domestic documents. These research methods will contribute to the collection, analysis and interpretation of data necessary to achieve the purpose of the article and solve the tasks. The results. The authors distinguish the following main stages: damage assessment (visual inspection, structural analysis, documentation of damage types, mapping, risk assessment); documentation (photo recording, descriptions, architectural drawings, historical research, use of digital technologies); valuation and prioritization; determination of strategies and approaches to preservation and restoration; technical and economic reasons; legal and ethical considerations; the implementation process and its planning (staged approach, allocation of resources, cultural sensitivity and respect, involvement of communities, consideration of the historical and socio-cultural context, inclusiveness, use of traditional techniques and materials, balance of preservation and reconstruction, long-term maintenance and monitoring). Basic requirements for the process of heritage restoration and preservation are defined. Principles of preservation and restoration of the cultural heritage of Ukraine in the conditions of post-war reconstruction are proposed. Scientific novelty. It is defined by a combination of principles of scientific restoration, post-war reconstruction of Ukrainian cities, creation of national identity and principles of sustainable development. Practical relevance. The results of the study will help local authorities and planners to make informed decisions regarding the reconstruction of Ukraine and the development of urban infrastructure. This can be important for the preservation of cultural heritage in cities. Understanding the basics of reconstruction can help attract investments for further development of cities.